(untitled) (International Journal of Built Environment and Sustainability, 2025)
This review critically examines the development and performance of building-integrated photovoltaic (BIPV) shading systems, with emphasis on adaptive design strategies, energy optimization, and aesthetic integration. Following PRISMA-2020, we conducted a systematic review of English, peer-reviewed literature in Web of Science and Scopus for 2010-2024. We identified 2,699 records; after removing 525 duplicates, 601 automation-flagged ineligible items, and 216 records for other reasons, 1,357 records were screened. We excluded 619 at screening, sought 738 reports for retrieval (411 not retrievable), and assessed 327 full texts for eligibility; 190 were excluded (non-empirical 114, not peer-reviewed 56, full text unavailable 20). The final corpus comprised 27 studies (137 included reports) (Figure 1). Key quantitative findings from these studies indicate cooling-load reductiorns of 10-77%; adaptive systems achieving ≈65% daylight autonomy with DGP ≤ 0.25; rooftop systems yielding 50-70% more electricity than vertical facades; semi-transparent east façades delivering sDA ≈ 50-60% with DGP ≈ 0.30-0.40; and south-facing arrays at 45° tilt reaching 104 kWh·m-²·yr-¹. Three trends emerge: (1) a shift toward adaptive façades using real-time, AI-driven controls to balance energy and visual comfort; (2) growing use of multi-objective simulation frameworks coupling energy, daylighting, and thermal analyses; and (3) heightened attention to aesthetic coherence and user perception. Despite progress, challenges persist in life-cycle validation, standardized evaluation, and cross-disciplinary integration. The paper concludes with a framework that couples dynamic-shading logic, architectural aesthetics, and performance-based simulation to guide future BIPV façade research. Unlike previous reviews that consider energy or daylight in isolation, this study integrates typological design, energy/thermal/visual performance, and aesthetic/user acceptance into one comparative framework, providing decision-ready ranges and trade-off matrices for BIPV shading.